Pengaruh Pengembangan Karir Terhadap Kinerja Karyawan Pada Pt. Bali Word Canggu - Purnawati, Ni Luh Gede Putu; Yudiastra, Putu Pande (Jurnal Mirai Management, 2024)
The aim of this research is to examine the influence of career development on employee performance at PT. Bali Word Canggu. Sampling used the census method, namely taking all employees of PT. Bali Word Canggu, totaling 33 people. Data were collected by distributing questionnaires using a Likert scale with a score of 1 to 5. The data analysis technique used was multiple linear regression analysis. The results of this research indicate that career development has a positive and significant effect on employee performance at PT. Bali Word Canggu. Keywords: career development, employee performance